2022
DOI: 10.3390/d14060465
|View full text |Cite
|
Sign up to set email alerts
|

Why Did Brown Hare Lepus europaeus Disappear from Some Areas in Central Poland?

Abstract: Brown hares originated in the open steppe grasslands of Eurasia and have adapted very successfully to a mixed, arable agriculture environment. In the last decades of the 20th century, a decline in brown hare populations has been observed in many European countries. In this study, we documented a long-term (1965–2018) decline in the hare population in a field and forest mosaic in central Poland (from over 30 ind./100 ha in the mid-1960s to 1–2 ind./100 ha in the past decade). We showed that the recent autumn de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Based on our results, it can be assumed that the endemic presence of EBHS, still one of the most important infectious diseases of hares, in addition to many other pathological factors [67] does not have such a negative impact on the decline in the population of these animals. At present, environmental changes are considered the main cause of a deep decline in brown hare populations [45]. Moreover, it can be concluded that, according to the data from other EBHS endemic infections [36], the high seroprevalence in the hares tested was the result of early and regular contact of young hares with EBHSV.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Based on our results, it can be assumed that the endemic presence of EBHS, still one of the most important infectious diseases of hares, in addition to many other pathological factors [67] does not have such a negative impact on the decline in the population of these animals. At present, environmental changes are considered the main cause of a deep decline in brown hare populations [45]. Moreover, it can be concluded that, according to the data from other EBHS endemic infections [36], the high seroprevalence in the hares tested was the result of early and regular contact of young hares with EBHSV.…”
Section: Discussionmentioning
confidence: 94%
“…Data available from some European countries from the last 50 years show a drastic decline in the abundance of free-living brown (Lepus europaeus) and mountain (Lepus timidus) hares due to environmental, and demographic reasons, as well as the effect of diseases [1,2,[45][46][47][48][49]. In Poland, a constant trend in the decline of the abundance of brown hares and grey partridges accelerated dramatically at the beginning of the 1990s [50,51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After application to crops, pesticides may volatilize, or droplets of sprayed pesticides may adhere to dust particles and be carried by the wind to other areas, posing a potential hazard to wildlife. Repeated application during a growing season results in regular exposure and accumulation of pesticides in the body (Gryz and Krauze-Gryz 2022 ). Brown hares use agricultural fields shortly after pesticide application.…”
Section: Discussionmentioning
confidence: 99%
“…Lepus europaeus was rarer than Lepus timidus during the 15th-18th centuries in Lithuania, but later, the brown hare became dominant [17]. According to Bluzma [18], the most abundant population of Lepus europaeus in Lithuania was in the 1970s, but since the 1960s the population of Lepus europaeus in many European countries has been declining as a result of multiple factors [12,[19][20][21][22][23], and therefore the need to regulate their populations has arisen [12,23]. Since 1989, hunting of Lepus timidus has been prohibited [24], and currently in Lithuania, only brown hares (Lepus europaeus) are hunted at a moderate intensity.…”
Section: Introductionmentioning
confidence: 99%